Pengaruh Modal, Kemandirian, dan Pendidikan Terhadap Motivasi Usaha Para Ibu Rumah Tangga Perumahan Villa Bunga Arengka Pekanbaru - Sukriani, Nurul; Febrina, Dian (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This research aims to determine the business motivation of housewives in the Villa Bunga Arengka housing complex, using the variables capital, independence and education to analyze their influence on entrepreneurial motivation. The population in this research is the Villa Bunga Arengka housewife who runs a home business, currently numbering 35 people. Data collection was carried out using a questionnaire method, namely by providing a list of statements to respondents. The data analysis technique used is multiple linear regression analysis operated through the SPSS 20 for Windows program. The results of the research show that simultaneously and partially the variables capital, independence and education have a significant effect on the entrepreneurial motivation of housewives in Tuah Madani District Pekanbaru